A study on English vocabulary teaching and learning at Danang premary schools - Nguyễn Thị Tú Trinh (2005)
This is a contrastive analysis of conceptual metaphors for “life, death, and time” in English and Vietnamese. This thesis aims at investigating the semantic features of “life, death, and time” in the frame …